Invasão de Lithobates catesbeianus na mata atlântica sul do Brasil : relações com espaço, ambiente e anfíbios nativos - Both, Camila Chiamenti (2012)
Biological invasions exponentially increased in the past century in the whole world, they became conspicuous in practically every ecosystem. By one side, invasive species may have few or none effects upon native communities. In the extreme opposite, they may cause deep structural changes, resulting in local or global species extinction. Thus, it is crucial to known patterns and process related with invasions, in order to take management decisions, when necessary, and/or to prevention new invasions. The understanding of invasion effects upon amphibian populations and communities its an urgent need. This group has been suffering with high rates of population declines and extinctions, and invasions are among the causation factors of this scene. Amphibians could be affected by a variety of non-native species, including amphibians itself. Lithobates catesbeianus, the American bullfrog, is an example of successful invasive species. The bullfrog is present in more than 40 countries throughout the world, including Brazil. The species introduction is often associated with aquaculture activities. Lithobates catesbeianus is a generalist predator; it may be a superior competitor in relation with many species at larval and adult phases; individuals could be vectors of diseases, which are lethal to many other amphibian species. In Brazil, the introduction occurred at 1935, when were imported the first specimens to initiate the first bullfrog farm. The bullfrog farming expanded in following decades, and individuals were translocated to diverse new Brazilian states. Many escapes and releases occurred, resulting in the invasive populations presence in a high number of municipalities. The goals of this thesis are: i) to characterize the current bullfrog distribution in Brazil; ii) to identify the main factors prediction the invasion spatial patterns, regarding abundance and presence of stablished populations; iii) to test for potential negative effects of bullfrog invasion upon amphibian richness; iv) to test if it bullfrog calls may promote competition in the acoustic niche. To attain these goals, besides data compilation from published studies and natural history collections (goal i), samplings were carried out in 90 waterbodies, in three Southern Atlantic Forest areas (goals i, ii and iii), and it was conduced an in situ experiment to test the effects of bullfrog advertisement calls upon a native treefrog advertisement call (goal iv). Based on data collected in field and data compiled from other studies, it was possible to diagnose that the species is present in a many higher number of localities than previous reported. The current spatial distribution patterns of L. catesbeianus abundance, in Atlantic Forest Areas, are mostly predicted by local waterbody descriptors, i.e. fine spatial scale. Spatial models and landscape descriptor also predict bullfrog abundance distribution, but are secondary factors. The same waterbody characteristics were predictors of established population presence. The waterbodies where bullfrogs were found in higher abundances did not showed lower native amphibian richness. The relationship between bullfrog postmetamorphic abundances and native amphibian richness was weak and positive. When spatial, environmental and community composition gradients were taken into account, the bullfrog-richness relationship reveled to be indirect. The bullfrog predicted gradient composition change, which in its turn predicted richness. Its possible to interpret that bullfrog is showing higher abundances in certain communities, and such communities with more bullfrog individuals are species rich. Lithobates catesbeianus showed association with common species, with wide geographical distribution, but was observed co-occurring with a variety of species, even at small abundances. During the experiment simulating an acoustic invasion, it was observed that bullfrog advertisement call may induce change in native frogs advertisement calls. Calling males of Hypsiboas albomarginatus, exposed to a sequence of bullfrog advertisement calls with five min. duration, showed alterations in note duration and frequencies of their calls. Once the advertisement call is the primary reproductive selection basis for many anurans, such change may imply in adaptative loss. The set of the results presented in this thesis, allowed a better diagnostic of Lithobates catesbeianus invasion in Brazil, indicating that its at late invasional stages. It was possible to observe that species distribution is responding to local filter, mostly waterbody features. None negative relationship with native amphibian richness was observed. Nonetheless, there is no data about communities status before invasion to make possible to assert that species loss did not occurred in the past. The results of acoustic invasion experiment are an example that invasion effects upon native species may be subtle.